Digital Leadership Transformation for Enhancing Organizational Performance in the Society 5.0 Era: A Systematic Literature Review - Herman T (Journal of Emerging Economics and Business, 2026)
Digital transformation has become a strategic agenda for organizations in responding to the increasingly complex challenges of the Society 5.0 era. The success of this transformation depends not only on technological adoption but also on leadership capability in effectively managing organizational change. This study aims to analyze the role of digital leadership transformation in enhancing organizational performance in the Society 5.0 era. A Systematic Literature Review (SLR) approach was employed by adopting the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were collected from scientific articles indexed in Scopus and Google Scholar published between 2021 and 2025. Following the selection process, 18 articles met the inclusion criteria and were analyzed using thematic analysis. The findings indicate that digital leadership serves as a strategic capability that drives organizational digital transformation through the development of digital vision, digital culture, and human resource capabilities. Digital transformation subsequently enhances organizational agility, operational effectiveness, innovation, and overall organizational performance. The study further reveals that, within the Society 5.0 context, organizational success is determined not only by technological advancement but also by leaders’ ability to integrate technology with human-centered values. This study contributes to the development of digital leadership literature and provides practical implications for organizations in designing sustainable and human-centered transformation strategies.